Boundaries of love : interracial marriage and the meaning of race - Osuji, Chinyere K. (New York University Press, 2019)
"Osuji's "Boundaries of Love" explores the issues of race and interracial marriage"-- Provided by publisher
Keywords: Čubrilović -- Familie : 19. Jh.-; Interracial marriage -- United States -- Case studies.; Interracial marriage -- Brazil -- Case studies.; Multiracial families -- United States -- Case studies.; Multiracial families -- Brazil -- Case studies.; Mariage interracial -- États-Unis -- Études de cas.; Mariage interracial -- Brésil -- Études de cas.; Familles métissées -- États-Unis -- Études de cas.; Familles métissées -- Brésil -- Études de cas.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; Interracial marriage; Multiracial families; Brazil; United States; Interkulturalität; Partnerschaft; Brasilien; USA; Familles mixtes -- États-Unis -- Los Angeles (Calif.); Familles mixtes -- Bresil -- Rio de Janeiro (Bresil); Mariage interethnique -- États-Unis -- Los Angeles (Calif.); Mariage interethnique -- Bresil -- Rio de Janeiro (Bresil); Electronic books.; Case studies; Case studies.; Études de cas.